Patient Room Design: A Qualitative Evaluation of Attributes Impacting Health Care Professionals. Issue 3 (July 2021) - Fay, Lindsey; Santiago, Joshua E.; Real, Kevin; Isaacs, Kathy
Abstract : The focus of this research was to identify what attributes of patient room designs are most beneficial to health care professionals and to explore whether particular professionals hold certain beliefs about patient room attributes. Acute care, progressive care, and intensive care patient room designs were analyzed through the use of pre- and postoccupancy evaluations of a cardiovascular service line. Fourteen focus groups and 1 interview among 74 health care professionals were conducted. Qualitative analysis of the data was guided by a multidimensional framework. A descriptive quantitative assessment was additionally made to reveal positive, negative, or neutral trends and determine the frequency of attributes discussed. The findings revealed outcomes in 4 primary areas: (1) clearance around the bed; (2) visibility; (3) access to the bathroom/bathroom configuration; and (4) access to daylight/views of the exterior. This study identified 8 additional categories. Outcomes illustrate perceptions from a myriad of health care professionals, but the nurses, therapists, and interdisciplinary members of the care team station offered the greatest depth of information. As patient room designs continue to evolve, building on evidence gathered as new or established models are evaluated will become increasingly important.